Clinical Characteristics and Mortality Predictors of Acute Respiratory Distress Syndrome Patients in ICU- an Observational Study - Rajbanshi, Lalit Kumar; Arjyal, Batsalya (Birat Journal of Health Sciences, 2023)
Introduction Adult respiratory distress syndrome (ARDS) is an inflammatory lung condition characterized by a sudden onset of severe oxygen deficiency, bilateral chest infiltrates, and high morbidity and mortality rates. The causes and prognostic factors for ARDS may vary in tropical regions. Objective This study aimed to investigate the causes, clinical characteristics, and outcomes of ARDS patients admitted in ICU. Methodology We conducted a prospective observational study involving 92 ARDS patients admitted to the medical and surgical intensive care units of a tertiary care hospital in eastern Nepal from 2021 to 2023. We included patients aged 15 years and above who met all the Berlin criteria for ARDS. Patients with burns, end-stage renal disease, hepatic disease, head injuries, congestive cardiac failure, and postoperative patients were excluded. We assessed demographic parameters, initial clinical presentations, causative agents, ventilation parameters, organ failure during the ICU stay, and factors influencing patient mortality. Result Our cohort had a mean age of 45.71 ± 20.02 years, with a predominance of male patients. The majority of patients presented with fever and shortness of breath. Approximately 26.1% had mild ARDS, while 25% had severe ARDS. The initial Sequential Organ Failure Assessment (SOFA) score was 10.11 ± 6.07, with most patients having a lung injury score of less than 2.5. Higher lung injury scores and low PaO2/FiO2 ratios were associated with increased mortality (P<0.05). The overall mortality rate in our study was 33.6%. Conclusion Pneumonia emerged as the most common cause of ARDS in our region. Low PaO2/FiO2 ratios and higher lung injury scores significantly influenced ARDS mortality.